La web como cerebro colectivo transdisciplinar - Castañeda Bustamante, Heiner (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
This essay establishes a discussion based on Edgar Morin’s concept of complex thinking, on transdisciplinarity and on the framework of the webspace, in which may kinds of knowledge meet, complement, contrast, unsubordinate and derive from each other, with the emergence of a collective brain represented in the participation of internet users made of bytes. The method of comprehension is manifested through the dialogue of lexical subjects, which evidences the otherness of knowledge expressed through the cosmogonies of human beings that are behind messages hosted in the highways of virtual information.